ANALISIS DETERMINAN PROPORSI TABUNGAN RUMAH TANGGA DI KOTA BENGKULU - Dewi Rahmayanti (The Manager Review, 2019)
This research was conducted on the community in the District of Gading Cempaka BengkuluCity that aims to determine the effect of income, the number of family members and age onthe proportion of household savings in the city of Bengkulu in particular the District ofGading Cempaka. Using a verification approach with multiple regression analysis tools and asample of 100 people. The results of the study stated that only the age variable had asignificant effect on the proportion of household savings.